The influence of relationship pattern labeling on intimacy, acceptance, and relationship satisfaction. (7th December 2022) - Rice, Jenna; McTernan, Melissa; Cordova, James
Abstract: Relationship health has a strong influence on physical and emotional health, and with reported rates of divorce at 40‐50%, relationship health is a critical public health issue. Thus, it is important to identify mechanisms that encourage healthy relationship functioning. This study measures the impact of engaging in discussions of challenging relationship patterns, or Relationship Pattern Labeling (RPL). Such discussions are embedded in existing interventions, and yet there is no literature, to our knowledge, that examines the impact of these discussions independently. Our results indicate significant small increases in intimacy ( p = 0.002), acceptance ( p < 0.001), and relationship satisfaction ( p = 0.003) when participants engaged in RPL. We present preliminary evidence that supports the current applications of RPL and indicates that it may be successfully extended into independent online interventions.